(untitled) - Hamilton, Angus (Boston, 1902)
This book introduce about outline of history, land and folk, a city of peace, costume, manners, and morals, education and crime. Korean industries, Korean scenery, mining and hunting, travelling in Korea...
Keywords: Hàn Quốc,Korea; Lịch sử,History